From Capsids to Complexes: Expanding the Role of TRIM5α in the Restriction of Divergent RNA Viruses and Elements - Kevin M. Rose; Stephanie J. Spada; Rebecca Broeckel; Kristin L. McNally; Vanessa M. Hirsch; Sonja M. Best; Fadila Bouamr (Viruses, 2021)
An evolutionary arms race has been ongoing between retroviruses and their primate hosts for millions of years. Within the last century, a zoonotic transmission introduced the Human Immunodeficiency Virus (HIV-1), a retrovirus, to the human population that has claimed the lives of millions of individuals and is still infecting over a million people every year. To counteract retroviruses such as this, primates including humans have evolved an innate immune sensor for the retroviral capsid lattice known as TRIM5α. Although the molecular basis for its ability to restrict retroviruses is debated, it is currently accepted that TRIM5α forms higher-order assemblies around the incoming retroviral capsid that are not only disruptive for the virus lifecycle, but also trigger the activation of an antiviral state. More recently, it was discovered that TRIM5α restriction is broader than previously thought because it restricts not only the human retroelement LINE-1, but also the tick-borne flaviviruses, an emergent group of RNA viruses that have vastly different strategies for replication compared to retroviruses. This review focuses on the underlying mechanisms of TRIM5α-mediated restriction of retroelements and flaviviruses and how they differ from the more widely known ability of TRIM5α to restrict retroviruses.